2006
DOI: 10.1002/jrs.1498
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of some benzohydroxamic acid derivatives on copper oxide: assignment and interpretation of SERS spectra

Abstract: The general aim of this work is to obtain information about the adsorption geometry of several benzohydroxamic acid (BHA) derivatives deposited on copper oxide. The investigation is done by means of surface enhanced Raman spectroscopy (SERS). In order to interpret the experimental information, an assignment of the SERS spectra is carried out. The process of assignment is supported by theoretical spectra derived from quantum-chemical calculations. As the size of the molecules and the overall lack of symmetry of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…However, the positions of some bands differ from those in the solution-phase spectrum, indicative of different strengths of interaction. Differences in interaction strength between BHA and metal ions in solution and at surfaces are also reported in the literature ( Blajiev et al., 2006 ). The band at 1,494 cm −1 ( Blajiev et al., 2006 ) suggests an involvement of the hydroxamate moiety in the interaction with the surface, consistent with ATR-FTIR and DFT results.…”
Section: Resultssupporting
confidence: 58%
“…However, the positions of some bands differ from those in the solution-phase spectrum, indicative of different strengths of interaction. Differences in interaction strength between BHA and metal ions in solution and at surfaces are also reported in the literature ( Blajiev et al., 2006 ). The band at 1,494 cm −1 ( Blajiev et al., 2006 ) suggests an involvement of the hydroxamate moiety in the interaction with the surface, consistent with ATR-FTIR and DFT results.…”
Section: Resultssupporting
confidence: 58%
“…Based on the previous report, the SERS enhancement for Ag nanoparticles is attributed to the electromagnetic and chemical enhancement mechanism [19][20][21][22][23]. On the other hand, many groups have reported that semiconductor can give rise to the enhanced Raman scattering of adsorbed molecules and the main contribution come in on chemical mechanism [24,25]. Furthermore, our group observed the SERS effect with 10 2 -10 3 orders of magnitude for CuO and ZnS nanocrystals [14,15].…”
Section: Resultsmentioning
confidence: 54%
“…6 The application fields of CuO nanocrystals are strongly dependent on its fundamental properties. Up to now, there are only a few reports 7,8 about CuO or, Cu2O with surface-enhanced Raman scattering (SERS) properties; however, the enhancement ability is ambiguous.…”
Section: -5mentioning
confidence: 99%